Sex-Specific Associations Between Serum Lipids, Antinuclear Antibodies, and Statin Use in National Health and Nutrition Examination Surveys 1999–2004 - Andersen, Catherine J.; Vance, Terrence M. (Frontiers in Medicine, 2022)
Lipid metabolism contributes to the regulation of leukocyte activity and immune responses, and may serve as a therapeutic target in the pathophysiology and clinical management of autoimmune disorders. In addition to lipid-lowering properties, statins have been shown to exert anti-inflammatory and immunomodulatory effects within the context of autoimmunity. Importantly, autoimmune incidence and lipid markers differ between men and women, suggesting that the relationship between lipid metabolism and immune function may vary by sex. Therefore, we investigated whether a predictive, sex-specific relationship exists between serum lipids, statin use, and antinuclear antibodies (ANA) – a routine clinical marker of autoimmunity and immune dysfunction – in U.S. men and women (> 20 years old; n = 1,526) from the National Health and Nutrition Examination Survey (NHANES) 1999-2004. Within this population, a greater proportion of women were positive for ANA (ANA+) and had higher ANA titers, as compared to men. While we did not observe statistical differences in average total cholesterol, LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C), or triglyceride levels in ANA positive (ANA+) vs. ANA negative (ANA–) men or women, we observed that a greater proportion of ANA+ women had high total cholesterol levels (>240 mg/dL) when compared to ANA+ men (13.0% vs. 9.0%), and that a greater percentage of ANA+ women had low HDL-C as compared to ANA+ men (29.2% vs. 19.6%). However, in logistic regression models, total cholesterol, LDL-C, and HDL-C levels were not able to predict ANA status, whereas elevated serum triglycerides (150 to < 200 mg/dL) were significantly less likely to be ANA+ vs. ANA– (OR 0.33; 95% CI 0.11-0.92) in men only. Interestingly, women who reported taking statins have significantly lower odds of being ANA+ (OR 0.25; 95% CI 0.09-0.76), whereas no significant association between statin use and ANA status was observed in men. Together, our findings provide novel insight into the relationship between lipid metabolism and autoimmunity by elucidating the limited, albeit sex-specific utility of routine clinical serum lipid levels to predict ANA status at the population level, while further identifying a sex-specific and protective role for statins in predicting ANA status in women.